A musical analysis of rhythmic, melodic, structural, and harmonic elements in Villa-Lobos' Gavota-Choro - Bin Shaharum, Salahuddin; Bin Mohd Yusoff, Mohd Yusran; Djahwasi, Herry Rizal (FBSB UNY, 2025)
This study addresses a significant gap in Villa-Lobos scholarship: the absence of detailed analytical studies examining how the composer specifically integrated European and Brazilian musical elements in his guitar compositions. While existing research acknowledges Villa-Lobos's cross-cultural synthesis, it rarely extends beyond historical contexts to provide systematic stylistic analysis of individual works. This research conducts a comprehensive stylistic analysis of Villa-Lobos's Gavota-Choro, examining precisely how the composer achieves the integration of European formal structures with Brazilian rhythmic and melodic idioms. The methodology employs multiple analytical approaches, including rhythmic analysis drawing on Sandroni's paradigmatic framework, harmonic analysis, and formal analysis adapted to account for both European and Brazilian structural principles. The analysis reveals Villa-Lobos's sophisticated integration techniques, including layered rhythmic structures, metric transformation, chromatic enhancement of traditional harmonies, and linear bassline construction. These findings contribute significantly to three domains: theoretical musicology, by demonstrating effective analytical approaches to cross-cultural musical synthesis; performance studies, by providing performers with deeper understanding of interpretative implications; and Latin American music scholarship, by illuminating how Villa-Lobos operationalized cultural integration in his compositional practice, establishing a model for national art music that honors both European traditions and indigenous expressions.Keywords: Villa-Lobos, Gavota-Choro, Brazilian classical guitar, cross-cultural musical synthesis, stylistic analysis